Anteromedial Portal versus Transtibial Drilling Techniques for Femoral Tunnel Placement in Arthroscopic Anterior Cruciate Ligament Reconstruction: Radiographic Evaluation and Functional Outcomes at 2 Years Follow-Up - Gabr, Ayman; Khan, Mohsin; Kini, Sunil G.; Haddad, Fares (The Journal of Knee Surgery, 2022)
The aim of this study was to compare the functional and radiographic outcomes of arthroscopic single-bundle anterior cruciate ligament reconstruction (ACLR) using either the anteromedial (AM) portal technique or transtibial (TT) technique. We identified 404 patients who underwent arthroscopic ACLR by a single surgeon between January 2006 and December 2016 at our institution. The TT portal was utilized in femoral tunnel drilling in 202 patients (TT group) while the AM portal was used in 202 patients (AM group). The mean postoperative follow-up duration was 26 months (range: 24–33 months). Postoperative radiographic femoral and tibial tunnel positions were assessed by two independent observers. Functional outcomes were evaluated with Tegner, Lysholm, and Knee Injury and Osteoarthritis Outcome score (KOOS) scores. On the anteroposterior plain radiographs, the mean femoral tunnel position relative to the lateral femoral condyle was 46.8% for the AM group versus 48.6% in the TT group, respectively (p=0.003). The mean graft inclination angle was 31.9° and 22° in the AM and TT groups, respectively (p<0.0001). On the lateral radiographs, the mean femoral tunnel placement across Blumensaat's line in relation to the anterior femoral cortex was 84% in the AM group while it was 78% in the TT group (p<0.0001). At 2 years postoperatively, there were no significant differences in the mean Tegner, Lysholm, and KOOS scores between the two patient groups. The graft failure rate at 2 years follow-up was 4.5% (n=9) in the AM group while it was 2.5% (n=5) in the TT group (p=0.2). Femoral tunnel placement was more anatomical with the AM portal technique compared with the TT technique. However, there was no significant difference in postoperative functional outcomes between the two patient groups. The AM portal technique appears to have a higher graft failure rate. This might be attributed to increased graft loading in an anatomical position.
Keywords: anterior cruciate; anteromedial; transtibial; anterior cruciate ligament